The Use of Virtual-Motivation to Engage Students on Lessons in Online Teaching - Ade Chandra (Universitas Muhammadiyah Barru, 2021)
This research is aimed at knowing whether the use of Virtual-Motivation (VM) is important or not. Furthermore, the second objective of this study is to find out whether the use of Virtual-Motivation can engage students to lessons. The data was collected through a questionnaire. Twenty seven students of tenth graders at SMA IT Al-Ishlah Maros participated in this research. The researcher used descriptive method to explore the students’ motivation which coming from their experiences in online teaching during the vovid-19 pandemic. The result of this research was presented descriptively to reveal the students’ perception and motivation comprehensively. The researcher found that virtual-motivation among tenth grades students at SMA IT Al-Ishlah Maros was important to engage them in learning English through online teaching. Most of students’ perception on the importance of the virtual-motivation was classified as high agree. Most students at SMA IT Al-Ishlah Maros were engaged through the use of virtual-motivation in learning English. It indicated that virtually-motivation was useful to engage the students in learning, and they were classified as high degree of motivation.